Thermal evolution of neutron stars described within the equation of state with induced surface tension. Issue 1 (31st January 2021) - Tsiopelas, Stefanos; Sagun, Violetta
Abstract: We present a modeling of the thermal evolution of the neutron stars, incorporating an effect of neutron and proton pairing. The considered equation of state with induced surface tension (IST) reproduces properties of normal nuclear matter, fulfills the proton flow constraint, provides a high‐quality description of particle yields created in heavy‐ion collisions, and is equally compatible with the constraints from astrophysical observations and the GW170817 event. The model features strong direct Urca processes for the stars above 1.91  M ⊙ . Our results show a very good agreement with the available cooling data, including observational data of the compact object in the center of the Cassiopeia A (Cas A), even without introducing nuclear pairing. The rapid cooling rate of the Cas A can be also reproduced by a 1.66  M ⊙ star with an atmosphere of light elements, high‐mass 1.955 − 1.96  M ⊙ stars with paired and unpaired matter, as well as by a 1.91  M ⊙ star with inclusion of neutron and proton pairings in the singlet channel.